Safety and efficacy of fecal microbiota transplantation for autoimmune diseases and autoinflammatory diseases: A systematic review and meta-analysis - Zeng, Liuting; Deng, Ying; Yang, Kailin; Chen, Junpeng; He, Qi; Chen, Hua (Frontiers in Immunology, 2022)
Objective: To evaluate the safety and efficacy of fecal microbiota transplantation for autoimmune diseases and autoinflammatory diseases. Methods: Relevant literature was retrieved from PubMed database, Embase database, Cochrane Library database, etc. The search period is from the establishment of the database to January 2022. The outcomes include clinical symptoms, improvement in biochemistry, improvement in intestinal microbiota, improvement in immune system, and adverse events. Literature screening and data extraction were independently carried out by two researchers according to the inclusion and exclusion criteria, and RevMan 5.3 software was used for statistics and analysis. Results: Overall, a total of 14 RCTs involving in 6 types of autoimmune diseases were included. The results showed that: (1) T1DM: compared with Autologous fecal microbiota transplantation (FMT) group (control group), the fasting plasma C peptide in Allogenic FMT group at 12 months was lower; (2) Systemic sclerosis: at week 4, compared with one of two placebo controls, three patients in the experimental group reported a major improvement in fecal incontinence; (3) Ulcerative colitis, Pediatric Ulcerative Colitis and Crohn's disease: FMT may increase clinical remission, clinical response, and endoscopic remission for patients with Ulcerative colitis, and increase clinical remission for patients with Crohn's disease. (4) Psoriatic arthritis: There was no difference in the ratio of ACR20 between the two groups. Conclusion: Based on current evidence, the application of FMT in the treatment of autoimmune diseases is effective and relatively safe, and it is expected to be used as a method to induce remission of active autoimmune diseases.